2022
DOI: 10.3390/math10193590
|View full text |Cite
|
Sign up to set email alerts
|

Two Interval Upper-Bound Q-Function Approximations with Applications

Abstract: The Gaussian Q-function has considerable applications in numerous areas of science and engineering. However, the fact that a closed-form expression for this function does not exist encourages finding approximations or bounds of the Q-function. In this paper, we determine analytically two novel interval upper bound Q-function approximations and show that they could be used efficiently not only for the symbol error probability (SEP) estimation of transmission over Nakagami-m fading channels, but also for the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Although normalΦLPER2x is narrower than normalΦLPER1x for 0.4993x1.7250 (see a previous study [12]), we found that the proposed lower bound remains closer than normalΦLPER2x over the same interval. For 0<x<1.7, the absolute error associated with Bercu (BE) bounds is very small compared to the other bounds.…”
Section: Numerical Comparisons and Conclusionsupporting
confidence: 43%
See 3 more Smart Citations
“…Although normalΦLPER2x is narrower than normalΦLPER1x for 0.4993x1.7250 (see a previous study [12]), we found that the proposed lower bound remains closer than normalΦLPER2x over the same interval. For 0<x<1.7, the absolute error associated with Bercu (BE) bounds is very small compared to the other bounds.…”
Section: Numerical Comparisons and Conclusionsupporting
confidence: 43%
“…Also, β1normalt=110normalt3+210t39normalt4+180normalt2+210 and β2normalt=113400t29t8660t6+1260t4+37800t2+113400. As noted by Bercu [11], the upper bound normalΦUBEx is valid only for 0x6.248. Peric et al [12] suggested a new lower bound for Φx based on the lower bound of Boyd [6] and the lower bound of Ruskai and Werner [7]. Their lower bound is given as follows: normalΦLPER1xΦx, where normalΦLPER1x=1minq1xq2x, q1x=πϕXx2x+()π22x2+2π and q2x=4ϕXx3x+x2+8…”
Section: Overview Of Some Bounds For φXmentioning
confidence: 99%
See 2 more Smart Citations
“…The cumulative distribution function (CDF) and its various forms (see Table 1 in the appendix) have significant applications in a wide range of fields [30], such as engineering [14,27,29], Mathematics [21], Statistics [4] computer science [15], diffusion theory [5], communication theory [26], physics [6], and chemistry [24]. Due to the mathematical complexity of the integral form, various approximations have been presented in the literature [19,11].…”
Section: Introductionmentioning
confidence: 99%